Relationship Between Organizational Climate and Communication Styles of Administrative Staff in Three Malaysian Universities - -, Tengku Marini (2007)
Communication plays a very important role within an organization since ambiguous communication may contribute to various organizational conflicts. Therefore, it is important to understand the communication style used by staff. As such the main purpose of the research is to study the relationship between organizational climate and communication styles among administrative staff of three selected universities. The specific objectives of the research is to determine the different perceptions of the organizational climate and communication styles among the staff based on their gender and types of departments; and to determine the contribution of communication styles, selected demographic factors and job related factors toward organizational climate individually and collectively. This study used quantitative research design and respondents were selected using the cluster sampling method. Based on Sullivan’s (2001) sampling table, a total of 235 administrative staff was selected from a total population of 909 administrative staff from three public universities in Klang Valley. An organizational climate questionnaire from Litwin and Stringer (1968) was adapted to measure the organizational climate, while communication style was measured using Norton’s (1983) communicator style measurement. Descriptive statistic, t-test, ANOVA, Pearson’s correlation and multiple regressions were used to analyze the data. The results revealed that male staff perceived organizational climate more favorable as compared to the females. Meanwhile, the friendly, precise and attentive style was found to be the predominant communication styles among the staff. The predominant organizational climate was achievement-oriented climate whereas friendly communication style was highly applied in all group types of departments. The friendly style, dominant style, impression leaving style and attentive style were correlated significantly to organizational climate. All communication styles, selected demographic and job related factors contributed significantly and collectively to the organizational climate. The finding indicates that achievement-oriented climate is prevalent in all the three universities and implies that action must be taken in order to create more favorable climate – the affiliation-oriented climate. The affiliation-oriented climate can be shaped through more frequent application of friendly communication style that will help to decrease conflict, and this climate is essential for human relations department since warmth and friendliness with minimum conflict is inherent in such climate. Furthermore, since the male staff has more contentious and open communication styles, it is suggested that the management should take into account the different style of communication between genders and focus their effort to narrow the gap.